Quantitative and Morphological Measures May Predict Growth and Mortality During Prenatal Growth in Japanese Quails - Arora , Kashmiri L.; Vatsalya, Vatsalya (International Journal of Poultry Science, 2012)
Growth pattern and mortality rate during the embryonic phase of avian species are difficult to recognize and predict. Determination of such measures and associated events may enhance our understanding of characteristics involved in the growth and hatching process. Furthermore, some quantitative measures could validate morphological determinants during the embryonic phase and predict the course of normal growth and alterations. Our aim was to characterize quantitative growth of embryos and to establish baseline embryonic standards for use in comparative and pathological research during the prenatal life of Japanese quail. Day 10 was a landmark timeline for initiation of extensive anatomical changes in growth and transformation. Wet and dry weights were positively correlated with each other and inversely correlated with water content (p = 0.05). Following d10, the water content decreased progressively, whereas, dry and wet weights increased with increasing age. Velocity of growth in wet and dry weights was evident starting d6, spiked at d11 and d15 and then declined before hatching on d16. Organic and inorganic contents of embryos were positively associated with age. Progressive increase in the organic to inorganic ratio with age was evident after d5, spiked on d9, d13 and d16. Accurate determinations of prenatal growth processes could serve as valuable tools in identifying morphological developments and characterization of prenatal growth and mortality, thus enhancing the reproductive efficiency of the breeding colony and the postnatal robustness of the offspring.